Succeeding in Foreign Language Study: Teachers and Students Standpoints - Vladimirova Larisa; Safin Rais; Ivanova Daria; Litvina Tatyana (SHS Web of Conferences, 2018)
The paper considers views of teachers and international students on effectiveness of language acquisition. The study represents the results of original experiment conducted among international students from the various institutes of Kazan Federal University. Students were requested to determine the priority of the following factors and explain the choice: a role of motivating anxiety for learning foreign language; a role of language abilities and talents of international student; a role of professional and personal characteristics of foreign language teacher; a role of methods, techniques and technologies of teaching; importance of studying within environment of a target language. Views of experts and international students on priority of impact of various factors of the foreign language teaching differed. The only factor where the opinions of teachers and students were the same, turned out to be the role of motivation. However, comparative analysis of factors of effectiveness in studying from the point of view of different and in the same time unified subjects of this process shows that the whole complex of factors must be taken into account. The results of the conducted study inevitably prove the necessity of considering the students’ opinion on the process of teaching, and corresponding correction of teachers’ activities.